THE EFFECT OF GLOBAL METHOD ON STUDENTS READING COMPREHENSION OF THE NINTH GRADE STUDENTS AT STATE ISLAMIC JUNIOR HIGH SCHOOL (MADRASAH TSANAWIYAH NEGERI/MTsN) 5 AT JAMBI CITY - MASLAHAH, INDAH (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
This study aims to assess the impact of employing the Global Method on students' reading comprehension at MTsN 5 Jambi City. It adopts a quantitative approach through a quasi-experimental design with non-equivalent control groups. The sample comprises 68 students divided into experimental and control groups selected via purposive random sampling. Data collection involves short-answer questions administered as pre-tests and post-tests. The findings indicate a higher mean post-test score (74.26) compared to the mean pre-test score (49.41). Statistical analysis using the Wilcoxon test reveals a significance level (sig 2-tailed) of 0.000, indicating acceptance of Ha1 (alternative hypothesis) and rejection of H01 (null hypothesis), signifying a significant improvement in students' reading comprehension after implementing the Global Method. Additionally, results from the independent sample t-test show a sig (2-tailed) value of 0.000, with a t-test value (6.074) surpassing the t-table value (1.671) at df = 66, leading to acceptance of Ha2 and rejection of H02. This confirms a significant difference in reading comprehension between students exposed to the Global Method and those who were not.